Bridging conventional medicine and complementary and alternative medicine. - Atsumi, K.
Complementary and alternative medicine (CAM) therapies are classified into five major domains: alternative medical systems (which includes traditional Chinese medicine, ayurveda, homeopathy, and naturopathy); mind-body interventions (including meditation, hypnosis, dance music, and art therapy); biologically based treatments (such as vitamins, minerals, herbs, and vegetarianism); manipulative and body-based methods (including chiropractic and massage therapies); and energy therapies - with some overlap across categories. Biomedical engineering (BME) is essential for exploring the safety and efficacy of these CAM therapies in the context of rigorous science. Recently, integrative medicine (IM) has been considered the ideal medical system for integrating conventional medicine and CAM. For this purpose, the concept of how to integrate these methods first must be investigated, and independent verification of CAM methods will be necessary. Biomedical engineering will be expected to be the most important method for verifying CAM scientifically.
Keywords: Alternative medicine; Art therapy; Ayurveda; Biologically based treatments; Biomedical engineering; Body-based methods; Chiropractic therapies; Complementary medicine; Conventional medicine; Dance music; Energy therapies; Herbs; Homeopathy; Hypnosis; Integrative medicine; Manipulative methods; Massage therapies; Meditation; Mind-body interventions; Minerals; Naturopathy; Traditional Chinese medicine; Vegetarianism; Vitamins